Modified Product Estimators for Population Mean in Simple Random Sampling Using Coefficients of Kurtosis and Skewness and Function of Quartiles of Auxiliary Variable - Srisodaphol, Wuttichai; Chuankrathok , Apidach; Worasan, Surunya (Agriculture and Natural Resources, 2015)
This paper deals with four new product estimators for estimation of the population mean in simple random sampling using the coefficient of kurtosis, the coefficient of skewness and the function of quartiles of the auxiliary variable. Mean square errors of the four proposed estimators are derived up to the first degree approximation and are compared with the modified product estimators proposed by Pandey and Dubey (1988); Upadhyaya and Singh (1999); Singh (2003); Singh and Tailor (2003); and Singh et al. (2004). The two proposed estimators performed better than those previous works. An empirical study has been carried out in support of the results.